2010
DOI: 10.1111/j.1469-8137.2010.03341.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs, the epigenetic memory and climatic adaptation in Norway spruce

Abstract: Summary• Norway spruce expresses a temperature-dependent epigenetic memory from the time of embryo development, which thereafter influences the timing bud phenology. MicroRNAs (miRNAs)are endogenous small RNAs, exerting epigenetic gene regulatory impacts. We have tested for their presence and differential expression.• We prepared concatemerized small RNA libraries from seedlings of two full-sib families, originated from seeds developed in a cold and warm environment. One family expressed distinct epigenetic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 49 publications
5
115
0
1
Order By: Relevance
“…Similar results have been reported for adaptation to freshwater in sticklebacks (Deagle et al 2012) and to high elevation in humans (Bigham et al 2010). Further bias may originate from excluding noncoding regions, microRNAs, or copy-number and presence-absence variants (including transposon insertions), which have been directly associated with adaptive responses in many taxa, including conifers (e.g., Yakovlev et al 2010;Fischer et al 2011;Hanikenne et al 2013). While genome-wide approaches are appropriate to capture most of this variability, having a satisfactory representation of the whole segregating genomic diversity is still a challenge for nonmodel species with large genomes, such as conifers (e.g., Birol et al 2013;Nystedt et al 2013; see also Tiffin and Ross-Ibarra 2014).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results have been reported for adaptation to freshwater in sticklebacks (Deagle et al 2012) and to high elevation in humans (Bigham et al 2010). Further bias may originate from excluding noncoding regions, microRNAs, or copy-number and presence-absence variants (including transposon insertions), which have been directly associated with adaptive responses in many taxa, including conifers (e.g., Yakovlev et al 2010;Fischer et al 2011;Hanikenne et al 2013). While genome-wide approaches are appropriate to capture most of this variability, having a satisfactory representation of the whole segregating genomic diversity is still a challenge for nonmodel species with large genomes, such as conifers (e.g., Birol et al 2013;Nystedt et al 2013; see also Tiffin and Ross-Ibarra 2014).…”
Section: Discussionsupporting
confidence: 77%
“…Finally, the incorporation of epigenetic variation into these predictive models must also be considered. Epigenetic factors have been shown to drive a substantial proportion of phenotypic variation and climate adaptation in Norway spruce (Yakovlev et al 2010), which seems particularly rich in gene families involved in DNA and chromatin methylation (Nystedt et al 2013). Thus, their role in modulating the expression of key adaptive genes in this and other taxa, including the candidates retained herein, still must be surveyed.…”
Section: Integrating Molecular Predictors Into Range-shift Modelsmentioning
confidence: 98%
“…Increasing evidence is accumulating that environmental maternal effects may be adaptive, enhancing the fitness of the offspring when established under environmental conditions that resemble the maternal environment (Galloway and Etterson, 2007;Herman and Sultan, 2011). This form of adaptive transgenerational plasticity has been reported in response to several biotic and abiotic environmental cues, including temperature (Yakovlev et al, 2010), drought (Herman et al, 2012), shade (Galloway and Etterson, 2007), nutrient availability (Kou et al, 2011), salinity (Boyko et al, 2010), herbivory (Rasmann et al, 2012) or viral infection (Kathiria et al, 2010). As a result of all these studies, environmental maternal effects are now recognized as a relevant source of phenotypic variation that may have an essential role in local adaptations (Herman and Sultan, 2011;Holeski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of previous studies about transgenerational plasticity in plants have been focussed on annual plants, and very little information is available on the magnitude and ecological relevance of this source of phenotypic variation in long-lived trees (but see Yakovlev et al, 2010;Cendán et al, 2012). Conifers are, however, an interesting model for the study of maternal effects (Yakovlev et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Johnsen et al (2005a) mentioned unpublished data suggesting that plants from warmer environment had higher levels of the overall DNA cytosine methylation. Yakovlev et al (2010) found and sequenced 16 micro-RNAs that showed different transcription levels between cold-environment and warm-environment Norway spruce individuals. They also confirmed that these miRNAs indeed affect transcription levels of their predicted target genes.…”
Section: Hitherto Knowledge Of Epigenetic Variation In Treesmentioning
confidence: 99%